A essencialidade da atividade judicante no Acordo de Não Persecução Penal - ANPP - Monteiro, Eduardo Martins Neiva (2024)
The research sought to identify and understand, based on the study of criminal procedural law, specialized doctrine and the jurisprudence of the Federal Supreme Court, the Superior Court of Justice and the Superior Military Court, the powers reserved to the Judiciary in the Non-Prosecution Agreement (ANPP). The Federal Constitution (principle of fraternity, principle of reasonable duration of the process and provision for the creation of special courts) was the starting point, as it is the primary basis of consensual criminal justice in the country. Decriminalizing institutes in force in some countries, from which the ANPP sought inspiration, and their application to certain crimes and situations that apparently had not been contemplated by the legislator were also analyzed. The study demonstrated that the role of the judge in analyzing the assumptions of existence and validity of the agreement is essential, granting it effectiveness, in the event of approval. The thesis is that the Federal Constitution and the legal rules of the ANPP, as well as the case law, especially of the Superior Court of Justice, require an active position from the judge regarding the verification of the legality of the negotiated solutions in all their aspects, given the power to assess the sufficiency and necessity of the agreement for the disapproval and prevention of the crime; judicial review is essential to provide the appropriate solution to the specific case.